Depression as an Embodied Experience: Identifying the Central Role of the Body in Meaning-Making and Identity Processes - Orphanidou, Maria; Kadianaki, Irini; O’Connor, Cliodhna (Qualitative health research, 2023)
Α significant part of the psychological research on mental health and illness is interested in how the body can impact one’s mental health. This impact is primarily explored using a biomedical framework, in studies that examine the body’s role in the emergence of a mental illness, the ways it can signify the presence of an illness (i.e. physical symptoms) and, finally, its role in the treatment process. Within this literature, the body is conceptualised as an object that can be diagnosed and treated. The current study approaches the body as a subject in the experience of depression. Specifically, it demonstrates that the experience of depression is embodied and that the body mediates meaning-making and identity processes. Using qualitative findings from eight interviews with Greek-Cypriot adults diagnosed with depression, we demonstrate that participants make sense of depression through their bodies, as a painful, uncomfortable and agonising experience. Further, we discuss how the struggle to regain control over the body, experienced as hijacked by depression, leads to a disrupted relation with the self and the world that expands beyond the idea of the loss of self, as described in the literature. Theoretical and clinical implications are examined.